Study on the Influencing Factors of Green Agricultural Subsidies on Straw Resource Utilization Technology Adopted by Farmers in Heilongjiang Province, China - Cheng Guo; Meng Li; Hong Chen (Agriculture)
Due to climate, resource endowment, planting habits, policy publicity, subsidies, and constraints, there have been many problems in the utilization of straw resources in the cold, main grain-producing areas in northern China. Based on the theory of value perception, an analytical framework was constructed, and the ordered logistic model was used to form an empirical analysis of the questionnaire data of more than 60 townships in 7 cities of Heilongjiang Province, trying to analyze the problems existing in the utilization of straw resources. The results show that the external factors include policy subsidy, policy punishment, and transportation convenience. Among the internal reasons, farmers’ personal characteristics, production habits, and perception of technical effectiveness and convenience have a significant impact on the application of straw resource utilization technology. Therefore, improving the intensity and precision of subsidies, strengthening the intensity of punishment, improving the popularization of technology, strengthening the ideological education of farmers to clarify the ecological value of straw resource utilization, and strengthening the construction of infrastructure to improve the convenience of transportation are effective means to promote straw resource utilization technology and promote the green transformation of agriculture.